ANALISIS PENANDA GRAMATIKAL DAN LEKSIKAL DALAM KUMPULAN CERPEN KOMPAS 2014 - Syulin Kinanthi; Atiqa Sabardila (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This article aims to: (1) analyze lexical cohesion and grammatical cohesion in the 2014 Kompas short story collection, (2) describe the meaning in the parts of lexical cohesion and grammatical cohesion. The subject of this research is the 2014 Kompas Short Story Collection with grammatical cohesion objects, namely references, substitutions; ellipsis; and conjunctions and lexical cohesion, namely repetition, synonymy, antonym, hyponymy, collocation. Data collection methods were carried out using qualitative methods using data collection techniques, namely reading and taking notes. The results of this study indicate that there are 49 grammatical cohesion data consisting of 5 data references (references), 6 data substitutions (substitutions), 5 omissions (ellipsis), and conjunctions (conjunctions) have the most data, namely 33 data. Meanwhile, lexical cohesion which consists of repetition has 5 data, 3 data synonyms, 6 data antonyms, 4 data hyponyms and 3 data collocations.Keywords: Literary Work, Cohesion, Grammatical, Lexical, Short Story